On the stability of harmonic maps under the homogeneous Ricci flow - Prado Rafaela F. do (De Gruyter, 2018)
In this work we study properties of stability and non-stability of harmonic maps under the homogeneous Ricci flow.We provide examples where the stability (non-stability) is preserved under the Ricci flow and an example where the Ricci flow does not preserve the stability of an harmonic map.